O "cientista amador" literal : a ciência para terraplanistas - Thiago Mikael Silva (2024)
Although science has become a collective activity in which consensus formation is crucial, there is no consensus on its definition. Various philosophical and sociological proposals to conceptualize science have emerged, but with each proposition, the boundaries between scientific knowledge and society have blurred. With the advancement of research on public perception of science, society has been questioned about its scientific understanding. However, this field of research still maintains a tradition of disdain for common sense, considering it deficient, erroneous, and distorted, with scientists tasked to correct it through communication and scientific literacy. Currently, this set of assumptions known as the Deficit Model is regularly challenged by the phenomenon of conspiracy theories driven by Web 2.0. The most emblematic case that has caught the media's and academics' attention is the flat Earth movement, which advocates for the flat Earth, challenging one of humanity's oldest scientific consensus. Contrary to the expectations of the Deficit Model, scientific understanding and literacy do not seem to reduce rejection of these consensuses. Based primarily on the Theory of Cognitive Dissonance, promising explanations have emerged to understand this phenomenon. Still, they have not deepened the dialogue with this and other theories in Social Psychology. Thus, starting with an effort to articulate assumptions of the Theory of Cognitive Dissonance and the Theory of Social Representations, this work sought to investigate and analyze the social representations of science for flat Earth advocates. Based on document analysis and assumptions of Social Network Analysis, a preliminary mapping of channels composing the network around the "Flat Earth" theme on YouTube was carried out using YouTube Data Tools modules. Subsequently, through a meticulous analysis with the aid of Gephi software, the 10 most relevant Brazilian flat Earth channels were selected in a network made up of 2,338 channels. 44 videos from these informant channels were qualitatively treated and simultaneously sampled and analyzed according to Grounded Theory and Audiovisual Materiality Analysis procedures. The results showed that flat Earthers produce and share their ideas about the flat Earth and other conspiracy theories mainly through vlogs, screencasts, and live streams on YouTube. Around the flat Earth, widely diverse and contradictory theories, ideas, and notions are clustered into an intricate belief system, making the flat Earth a meta-conspiratorial theory. However, there is evidence that the same process that produced this meta-conspiratorial theory may also have stimulated the conversion of individuals to the flat-earth-ism perspective. By adhering to a literal reading of the Bible, flat Earthers seem to experience a conflict between the account of a flat Earth suggested by Hebraic cosmology and the descriptions of modern science. After deciding in favor of the absolute truth of the Bible, there arises the need to justify this choice and explain how science became false, indicating a confrontation with cognitive dissonance. The rejected alternative is depreciated through a causal attribution that implies a conspiracy. On one side, a social representation of "true science" is elaborated, aligned with the Bible, epistemologically "empirical," methodologically "experimental," socially "simplified," and ethically concerned with the "improvement" of the human condition. On the other side, an alternative social representation of "false science" is produced, aligned with a malign system, "non-empirical," and "adulterated" to conceal the "true science." However, new and unsettling inconsistencies arise, either due to the implications of the group's position or through contact with contradictory perspectives brought by the alter. In the first case, a broad arsenal of inconsistency management mechanisms is mobilized, reducing them or finding a way to maintain them without generating cognitive dissonance. In the second situation, the Ego/Alter distance is regulated by semantic barriers and radical representations of otherness. Consequently, by compromising social comparisons, this distance creates conditions for self-contradiction. The group accuses its opponents of being dogmatic and superstitious while not seeming to realize the complacency of their belief system with positions and ideas that could subject them to the same accusation. In short, the outcomes of this study point doubly to the need to revise the assumptions of public policies related to scientific communication and for new studies that empirically and experimentally delve into the aspects of the proposed theoretical framework in this study.